Zambia Country Program Evaluation FY04-13 : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2016)
From 2004 to 2012, Zambia experienced a combination of good economic policies and high rates of growth not seen since the early years after its independence. While growth was mainly driven by rising copper prices, other factors contributed to Zambia’s ability to take advantage of this growth. The international debt relief programs in 2004-2005 almost eliminated public debt and provided the fiscal space for selective, high-priority investments and expanded social programs. The privatization of the copper mines brought new investment in rehabilitation and expansion of production. The period also saw a substantial expansion of primary education and progress in dealing with the most pervasive public health problems. These positive developments set the stage for Zambia to tackle its pervasive poverty. In practice, however, sustained growth over the period has led to little poverty reduction, especially in rural areas of the country. The Bank Group and other donors provided critical support at the beginning of the evaluation period, when Zambia’s debt level became unsustainable. The Bank provided substantial support for capacity development and better functioning institutions. The Bank’s efforts to strengthen public administration and improve governance met with some partial successes in enhanced audit and procurement capacity, and the achievement of Extractive Industries Transparency Initiative compliance. However, despite nearly a decade of implementation, the Integrated Financial Management Information Systems (IFMIS), is still only partially operational. Further, the Zambian government has not followed through on its positive discourse regarding decentralization of government authority.